3D Model Optimization for Hybrid Layer Printing - Lukosiunas, E.; Bulbenkiene, V.; Andziulis, A.; Harja, J. (Elektronika ir Elektrotechnika, 2012)
In today modern manufacturing the use of virtual models in prototype development has been increased. Hybrid Layered Manufacturing (HLM) - is a new way to create prototypes of virtual objects. 3d modelling programs are not optimized enough for creating objects by layers. One of the problem is a flat surface printing, because during that process beads are printed which have a parabolic shape. That shape is unsuitable for creating a flat surface. The paper proposes a method that will allow to print layers with flat surface. For this purpose an analysis and calculations were made with the help of a written algorithm, which was used in virtual environment testing it on 3d models. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2814